This Is What a Feminist (Space) Looks Like: (Re)conceptualizing Women's Centers as Feminist Spaces in Higher Education. Issue 6 (January 2014) - Nicolazzo, Z; Harris, Crystal
<x xml:space="preserve">Abstract</x> By sharing an honest, thoughtful dialogue about how their different identities affect their experience of feminism and feminist spaces, Z Nicolazzo and Crystal Harris model duoethnographic dialogue—a type of dialogue across difference that has the potential to be a catalyst for transformative student learning.